Technological Innovation And Firm Development: The Case Of Infovalley Digital Autopsy System Commercialisation - Adham, Khairul Akmaliah; Said, Mohd Fuaad (Asian Academy of Management (AAM), 2008)
Current research emphasises the importance of the successful commercialisation of technology in the development of small firms and the need to address unique contextual dimensions when examining the concept of commercialisation. Guided by product and venture development lifecycle models as well as a structuration perspective, this case study examines how an entrepreneurial venture called Infovalley Life Sciences develops and commercialises the firm's digital human autopsy system despite the fact that the firm operates within an underdeveloped innovation system context. In-depth interviews were conducted with key individuals involved in the innovation and venture development processes. Analysis indicates that the entrepreneur and his or her team co-evolve with their business contexts in creating a favourable nvironment for themselves. This process requires the entrepreneur to integrate his or her broad knowledge of technology applications and the market with his or her team's highly specialised knowledge in the core technology domain; this process results in a successful product launch. This leads to the creation of internal core capability, which supports the commercialisation of new products and thereby contributes to the firm's development and growth. This link between structuration and resource-based perspectives of entrepreneurship augments the conceptualisation of entrepreneurship, technological innovation and firm's development